PEMBELAJARAN MENGGUNAKAN MODEL LEARNING CYCLE 5E UNTUK MENINGKATKAN HASIL BELAJAR IPA DI SEKOLAH DASAR - Dea Mustika (JURNAL HANDAYANI PGSD FIP UNIMED, 2017)
Abstract : This research applied Learning Cycle 5E model in science learning to improve student learning outcomes in elementary school. Science learning requires real interaction between students and the subjects being studied, with the aim that students are trained to solve problems and think scientific. Learning Cycle 5E model is a model with a constructivist view that each stage can achieve the goal of science learning. The type of this research is Classroom Action Research using qualitative and quantitative approach. The research was carried out collaboratively with the research subjects were teachers and students of grade V SD. The results of the study showed an increase in student learning outcomes in science learning after applying the Learning Cycle 5E model. This shows the model of Learning Cycle 5E can be an alternative in the implementation of science lesson in elementary school. Keywords : IPA, Learning Cycle 5E Model, Learning Outcomes Abstrak : Penelitian ini menerapkan model Learning Cycle 5E dalam pembelajaran IPA untuk meningkatkan hasil belajar siswa di Sekolah Dasar. Pembelajaran IPA memerlukan interaksi nyata antara siswa dengan obyek yang dipelajari, dengan tujuan agar siswa terlatih untuk memecahkan masalah dan berfikir ilmiah. Model Learning Cycle 5E merupakan model dengan pandangan konstruktivis yang setiap tahapannya dapat mencapai tujuan dari pembelajaran IPA. Jenis penelitian ini adalah Penelitian Tindakan Kelas dengan menggunakan pendekatan kualitatif dan kuantitatif. Penelitian dilaksanakan secara kolaboratif dengansubjek penelitian adalah guru dan siswa kelas V SD. Hasil dari penelitian menunjukkan terjadi peningkatan hasil belajar siswa dalam pembelajaran IPA setelah menerapkan model Learning Cycle 5E. Hal ini menunjukkan model Learning Cycle 5E dapat menjadi alternatif dalam pelaksanaan pembelajaran IPA di SD. Kata Kunci : IPA,Model Learning Cycle 5E, Hasil Belajar